The effect of using the Microsoft Teams application on the collaboration skills of certified independent learning/project students at PT Maribelajar Indonesia Cerdas - Nurkhamamah, Zerina; Wahyuningtyas, Neni (Universitas Negeri Malang, 2024)
The Industrial Revolution 4.0 makes learning more accessible, such as using technology. The technology used in learning can improve students' skills. Skills are essential for every student to improve the quality of learning in the 21st century. The quality of learning in the 21st century can be enhanced through the Freedom to Learn - Independent Campus (MBKM) program, which provides space for students in Indonesia to develop the 5C skills, namely creativity, critical thinking, communication, collaboration, and celebration. One of the MBKM programs you can participate in is the Certified Independent Study/Project Internship Program (MSIB) with partner PT MariBelajar Indonesia Smart in collaboration with Microsoft. The MSIB Program uses Microsoft Teams to help students collaborate to solve problems through capstone projects. The research method uses quantitative methods and aims to analyze the effect of Microsoft Teams on the collaboration abilities of PT Independent Study/Project students. Let's Learn Smart Indonesia. The research subjects were PT Independent Study/Project students. MariBelajar Indonesia Smart Cycle 2. The instrument used to measure the use of Microsoft Teams and collaboration skills is through a questionnaire with a Likert scale. The data analysis technique used is simple linear regression using the SPSS 23.0 for Windows program. The analysis results show that using Microsoft Teams affects students' collaboration abilities, which can improve their skills and help them complete projects. Using Microsoft Teams helps students utilize collaboration spaces to understand Microsoft Teams' features to enhance their communication skills and creativity. Future researchers should test other factors such as communication skills, creativity, and critical thinking skills using Microsoft Teams. Students can explore Microsoft Teams features to complete other course assignments.